Progress in the clinical application of immune checkpoint inhibitors in small cell lung cancer - He, Jiahui; Hu, Qinyong (Frontiers in Immunology, 2023)
Small cell lung cancer (SCLC) is a refractory cancer with poor prognosis due to its aggressive malignancy and high rates of metastasis, recurrence and drug resistance. These characteristics have also greatly impeded the identification of new treatment methods and drugs. The traditional model of SCLC treatment that has been reliant on platinum combined with etoposide for decades has been superseded by the emergence of immune checkpoint inhibitors (ICIs), which have shown significant therapeutic effects and broad application prospects as a monotherapy. This has led to the evaluation of ICIs with different mechanisms of action and their use in combination with radiotherapy or a variety of molecular targeted drugs to achieve synergy, complementary advantages, and reduce adverse reactions. Here, we review the progress in the use of ICIs as a monotherapy or in combination therapy for SCLC and consider the current limitations of these approaches as well as prospects for future developments.